Galaxy clusters at z ∼ 1 imaged by ALMA with the Sunyaev–Zel'dovich effect. (2nd February 2023) - Kitayama, Tetsu; Ueda, Shutaro; Okabe, Nobuhiro; Akahori, Takuya; Hilton, Matt; Hughes, John P; Ichinohe, Yuto; Kohno, Kotaro; Komatsu, Eiichiro; Lin, Yen-Ting; Miyatake, Hironao; Oguri, Masamune; et al.
Abstract: We present high angular resolution measurements of the thermal Sunyaev–Zel'dovich effect (SZE) toward two galaxy clusters, RCS J2319+0038 at z = 0.9 and HSC J0947−0119 at z = 1.1, by the Atacama Large Millimeter/submillimeter Array (ALMA) in Band 3. They are supplemented with available Chandra X-ray data, optical data taken by Hyper Suprime-Cam on Subaru, and millimeter-wave SZE data from the Atacama Cosmology Telescope. Taking into account departures from spherical symmetry, we have reconstructed non-parametrically the inner pressure profile of two clusters as well as electron temperature and density profiles for RCS J2319+0038. This is one of the first such measurements for an individual cluster at z 0.9 . We find that the inner pressure profile of both clusters is much shallower than that of local cool-core clusters. Our results consistently suggest that RCS J2319+0038 hosts a weak cool core, where radiative cooling is less significant than in local cool cores. On the other hand, HSC J0947−0119 exhibits an even shallower pressure profile than RCS J2319+0038 and is more likely to be a non-cool-core cluster. The SZE centroid position is offset by more than 140 h_70^-1 kpc from the peaks of galaxy distribution in HSC J0947−0119, suggesting a stronger influence of mergers in this cluster. We conclude that these distant clusters are at a very early stage of developing the cool cores typically found in clusters at lower redshifts.